Impact of Performance-Based Capitation Policy on Referral Health Services for Diabetes Mellitus Participants in the National Health Insurance Program - Pratama, Febriansyah Budi (Journal Research of Social Science, Economics, and Management, 2025)
The increase in the number of patients with Diabetes Mellitus, including the burden of service costs, encourages the implementation of policies to carry out secondary prevention at the primary health level, including implementing the Performance-Based Capitation (KBK) policy. This study aims to evaluate the KBK policy implemented in the National Health Insurance (JKN) program on health services for Diabetes Mellitus patients at Referral Health Facilities, using the Regression Discontinuity in Time (RDIT) method on BPJS Kesehatan Sample Data from 2015 to 2020. It was found that the implementation of the policy was not accompanied by a decrease in the level of health service visits at FKRTL, which was expected to occur after the implementation of KBK. These findings align with the results of qualitative deepening through in-depth interviews, where there are obstacles in the implementation of KBK in First-Level Health Facilities (FKTP), especially in encouraging the improvement of Diabetes Mellitus services. Improvements in KBK policies are needed both in determining indicators, targets, and other supporting policies in achieving FKTP performance to encourage improvement in the output of Diabetes Mellitus health services at FKTP.